Reframing Qur'anic Perspectives on Interfaith Relations in the Contemporary World: A Thematic Analysis - Al-Ghoni, Burhanudin; Hermawan, Ahmad; Nugroho, Kharis; Azhari, Husain; Awliya, Fathiya Azka; Zambri, Shafiqah Amiera Binti Mohd (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study examines the Qur'anic perspectives on interfaith relations in the contemporary world, emphasizing the relevance of its principles in addressing modern pluralistic societies. Islam, as a divinely revealed religion, acknowledges the existence of other faiths while upholding the theological stance that Islam is the only religion approved by Allah. The Qur'an recognizes religious diversity as part of divine will and explicitly rejects coercion in matters of belief, positioning the prophets solely as conveyors of God's message. Employing a thematic interpretation (tafsir maudhui), this study systematically collects and analyzes Qur'anic verses related to interfaith relations. This method enables a structured and comprehensive understanding of key principles such as tolerance, peace, equality, deliberation, and justice. The analysis reveals that the Qur'an promotes peaceful coexistence and ethical engagement with non-Muslims while maintaining doctrinal exclusivity in matters of faith (aqidah). Theoretically, this study enriches discussions on Qur'anic hermeneutics by contextualizing interfaith themes within contemporary realities. Practically, it offers insights for policymakers, religious leaders, and scholars seeking to promote constructive interfaith engagement based on Islamic teachings. Contribution: The findings contribute to contemporary Islamic discourse by demonstrating how Qur'anic principles can serve as a foundational framework for fostering interreligious dialogue and social harmony in an era of increasing global religious diversity.